Spiders in Brazil: from arachnidism to potential therapeutic use of their venom part 1 of 2 - Ferreira Trindade, João Victor; Alves Ferrareis, Lis; Carvalho de Andrade, Ana Karolina; de Moraes Scopel Borges, Julia; Salvador Pereira Montenegro, Stefânia; Soares de Souza Lima Rodrigues, Bruna; Balbino Miguel, Paulo Sérgio; Siqueira-Batista, Rodrigo (Revista de Patologia Tropical / Journal of Tropical Pathology, 2022)
Spider envenomation, generically known as arachnidism, is described in many places around the world. In terms of medical importance, the following genera of animals stand out as the main origin of the morbid condition: Atrax (Sidney funnel web spider), Steatoda (false black widow), Latrodectus (black widow), Loxosceles (brown spider) and Phoneutria (armed spider), the last three causing accidents involving spiders in Brazil. This article, part 1 of 2, aims to present the main aspects of arachnidism in the country, with an emphasis on the biology and geographical distribution of spiders, biochemistry of the venom, pathogenesis and epidemiology of arachnidism, as well as prevention of the morbid condition. KEY WORDS: Arachnidism; araneae; spider bites; spider venoms.